Pengaruh Metode Pembelajaran Multimedia Cardiopulmonary Resuscitation (CPR) Terhadap High Quality CPR - Guruh Wirasakti Guruh Wirasakti (Jurnal Kesehatan dr. Soebandi, 2020)
The nursing students' ability to do high-quality Cardiopulmonary Resuscitation at dr. Soebandi School of Health Science (STIKES) Jember is still low so that providing knowledge and skill of high-quality cardiopulmonary resuscitation compression performed by nursing students is important. One of the strategies is giving cardiopulmonary resuscitation training with the multimedia learning method. This study aimed to identify differences in high-quality Cardiopulmonary Resuscitation using multimedia learning method training. This research used pre and posttest Quasy-experimental without control group method involving 36 respondents with a purposive sampling technique. The data was taken by pretest and posttest to measure between before and after training. The data analyzed by using the Wilcoxon test. The result shows that the rate of chest compression before intervention is 4 (12%), the rate of chest compression after the intervention is 33 (92%) with a level of p=0.000. The rate deep chest compression and the minimal interruption after the multimedia learning methods are 30 (83%) and 33 (92%). This study shows that multimedia learning methods training can improve the rate of chest compression, deep chest compression, and minimal interruption of high-quality cardiopulmonary resuscitation skills.